Konsep Dakwah pada Masyarakat Samarinda - M. Abzar (FENOMENA, 2013)
In common, sermon materials that presented  by the Khatib in the city of Samarinda refer to four subject themes, namely; theology / faith, religious service /syariah, morality, and current problems (education, economy ,  politics, and environment). The result of this research shows that theology problem / faith is the most common themes lectured which constitutes 40 %, the current themes around 25 %; behavior theme around 20 %; and religious service theme/ syariah around 15 %.